Response to Kiełpińska and Kowalski: A stab in a self-imposed darkness - Anders Galatius (Elsevier, 2021)
In a recent paper in Ecological Indicators, Kiełpińska and Kowalski (K&K) present a model aimed to facilitate culling of a large fraction of the Baltic grey seal population without sacrificing management aims with regard to distribution. Their paper and model include several flawed assumptions with regard to grey seal biology, particularly life history, population structure and movements. The actual modelling exercise is intransparent and there is no discussion or account for uncertainties or ecological complexities. K&K do not mention or review the existing literature on the outcomes of marine mammal culls or investigations of the role of grey seals in the Baltic Sea ecosystem, but state an imperative that aquatic top predators must be controlled. Ecosystem modelling has indicated that fisheries and a large grey seal population can coexist and that culling of marine top predators can have unpredictable and unintended effects. Given the flawed assumptions, lack of regard for uncertainty and complexity as well as the actual knowledge gaps, we suggest great caution in the use of K&K’s model.